A importância da educação ambiental no processo de ensino aprendizagem nas séries iniciais de uma escola pública no município de Inhangapi - PA - OLIVEIRA, Tenilde Gusmão de (2020)
This study aims to demonstrate the basic concept of the environment and its importance in basic education. Initially a memorial of life was reported and soon after reflections of lived experiences, talking about environment in the school scope. For environmental education is a process by which the learner begins to acquire information about environmental issues and thus has a new vision of what the environment is. It aims to sensitize the school about the importance of Environmental Education in the Teaching Learning Process in the Early Years of a public school in the Municipality of Inhangapi-PA. At the methodological level, the dialectical tendency was used, with a qualitative approach, with an exploratory character. The target audience was the 13 education workers who work in the said School, who participated in bimonthly meetings with the community, here called talk wheels, which produced inputs that are analyzed throughout the text. Some of these data have been added and this work as reports and are characterized in speeches, ranging from E1 to E13 and soon analysis show that people are aware that things do not go well, but also find themselves unable to intervene in reality . The study allowed a new knowledge of what the environment is and what it has to offer society and all who live in it and, from this, it will be possible to think and work on new strategies to advance the process of learning, which encourage environmental preservation through education.